Międzynarodowa transmisja kryzysów gospodarczych na poziomie przedsiębiorstw - Mazurek, Szymon (International Transmission of Crises on Business Level, 2005)
Globalisation and internationalisation of enterprises make connections between firms from different countries stronger and more numerous. These connections can have positive as well negative effects. During economic crises shocks can be transmitted directly to firms around the globe. This paper lists and describes five channels of firm-level transmission of crises: product competitiveness, an income effect, a credit crunch, a forced portfolio recomposition and a wake-up call effect.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 184-190